Assessment of the effect of various cerebroprotectors on the dynamics of cerebral and central hemodynamics in traumatic brain injury in rats - S. I. Semenenko; O. A. Khodakivskyi; A. I. Semenenko; O. M. Semenenko (Zaporožskij Medicinskij Žurnal)
Now the issue regarding the choice of effective cerebroprotective agents for traumatic brain injury (TBI) remains insufficiently studied.